Estudando a MPB: reflexões sobre a MPB, nova MPB e o que o público entende por isso - Saldanha, Rafael Machado (2008)
The purpose of this research is to discuss the evolution of the use of the abbreviation MPB (Música Popular Brasileira – Brazilian Popular Music), since its popularization, on 60’s, until the present days, by placing emphasis on its recent ramification as known as 'Nova MPB'. It also tried to understand how its reception by the Brazilian public works, trying to contrast the information gotten in the bibliographical research with the opinion of MPB listeners congregated in an Internet group.